DEVELOPMENT OF ECONOMIC SYSTEMS – IMPULSES AND ALTERNATIVES - Piovarciova, Veronika (European Scientific Journal, ESJ, 2014)
At the end of the twentieth century, it comes to an overlap of several important, qualitatively new processes in the global economy. Processes of globalization, integration and interdependence. The nature of advanced economies changes fundamentally towards knowledge-based economy as the basis of a knowledge society. Global transformation conditioned by technological, economic, social and institutional change is taking place in all the real functioning economic systems. Determinants of their socio-economic arrangements are changing significantly, relativising different premises of functioning of economic systems considered essential and unchanging until recently. In pursuing the development of economic systems as crucial can be seen the element of their ability to adapt dynamically to the development of very complex and changing conditions. Adaptive capacity of systems is key to longterm growth. This article takes a look at some important impulses and changes going on in the real functioning economic systems since the end of the 1950s, that gradually led to a global crisis. It also introduces some opinions on how should an alternative to current economic system look like.